PGSD FKIP UNRI STUDENTS’ ATTITUDES IN ONLINE LEARNING DURING THE COVID-19 PANDEMIC - Latifah Hidayati; Guslinda; Zufriady (Jurnal PAJAR (Pendidikan dan Pengajaran), 2023)
The virus is currently spreading around the world and has been labeled as a pandemic by the World Health Organization (WHO). Every activity is conducted at home, which is called Work From Home (WFH). The transition in the educational system from direct to online learning does certainly influence people’s attitudes, which are the indicator of successful learning. It includes knowledge, comprehension, attitudes, and so on. Based on the description, it was conducted the research entitled "Analysis of Attitudes of PGSD FKIP UNRI Students in Online Learning During the Covid-19 Pandemic". Based on the background of the problem, the formulation of the research problem was "how are the attitudes of PGSD FKIP UNRI students in online learning during the covid-19 pandemic?". The type of research used a survey method with a questionnaire as the data collection tool by using a quantitative approach descriptively, which is written words. The research was conducted at PGSD FKIP of Universitas Riau in the odd semester of the 2021/2022 academic year. The population and sample involved 119 students in the year 2019 of PGSD FKIP UNRI. According to the research results, the average score was 67.17 with a good category. At the first indicator, cognitive indicates 74.8 in the good category. At the second indicator, affective implies 67.3 with the good category. At the third indicator, the conative shows 59.42 in the good enough category.